Pengaruh Media Sosial Terhadap Akhlak Siswa Madrasah Aliyah Salafiyah Wonoyoso - Istiqomah, Rafika; Fatimah, Siti (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The purpose of this research is to find out how social media impacts on students' morals at Madrasah Aliyah Salafiyah. This quantitative research uses a regression approach to show the effect of variable X and variable Y. The number of respondents in this study amounted to 84 students, including 20 students of class X.01 and 20 students of class X.02, 23 students of class XI IPS and 21 students of class XI IPA. Determination of the sample using purpose sampling technique, while the data collection technique uses a questionnaire. While data analysis techniques using inferential data analysis techniques using simple linear regression analysis. The results showed that there was an influence of social media on student morals at Madrasah Aliyah Salafiyah Wonoyoso Kebumen, with a significance value of 0.000. Based on the results of the determination correlation coefficient test (r2) of 25%. Which means it can be said that 25% of student morals are influenced by social media. While the remaining 75% is influenced by other variables. So it can be concluded that there is an influence of social media on student morals at MA Salafiyah Wonoyoso Kebumen.